Strategi Dinas Sosial Dalam Penanganan Anak Jalanan Di Kota Tanjungpinang - Thariq Riawan; Jamhur Poti; Ramadhani Setiawan (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Street children are not a pleasant choice because they are in a state of uncertainty about their future, and their existence is not a "problem" for many, etc. future, and their existence is not a "problem" for many parties, and others. The research objectives in conducting this research is to find out what strategies the Social Service uses to deal with street children in Tanjungpinang City. Tanjungpinang City to deal with street children in Tanjungpinang City. Seeing the conditions that street children conditions experienced by street children, the Tanjungpinang City Government, especially the Tanjungpinang City Social Service, made a Tanjungpinang makes handling street children with real handling will create a programme strategy to alleviate street children in Tanjungpinang City. create a programme strategy to alleviate the problem of street children by using the theory of Jack Kooten (2002). using the theory of Jack Kooten (1991: 81). This research method is explained by using a qualitative approach. Literature Study, Field Observation, Interview and Documentation. The results Research that has been conducted by researchers, namely (1) Organisational Strategy obtained by the Social Service to carry out development within the Internal Service to carry out and help street children in Tanjungpinang City, (2) Programme Strategy, as for the programmes offered by the City of Tanjungpinang Social Service, namely Tanjungpinang is a Support Group that functions to foster street children. street children. (3) Resource Support Strategy, has not run optimally. Although there are already several supporting resources such as 2 street children, but they cannot cover all street children. and finally (4) Institutional Strategy, in the institutional structure in the Social Service has a vision and mission that is adjusted to the vision and mission of the street children. Social Service has a vision and mission that is adjusted to the Strategic Plan (RENSTRA) of the Social Service. (RENSTRA) of the Tanjungpinang City Social Service. It can be concluded that the strategies contained in the implementation of the Social Service in handling street children in Tanjungpinang City has not run optimally.